MODEL OPTIMISASI UNTUK MASALAH MINIMISASI BIAYA PERJALANAN WISATA TUR-TUNGGAL DI ZONA KEPULAUAN - M Thezar Afifudin; Dian P. Sahar (ALE Proceeding, 2021)
This study aims to develop an optimization model for solving the insular cost minimization single-tour travel problems. The model was developed using an integer non-linear programming approach by considering the selection of departure and arrival points of an island, selecting accommodation points, selecting transportation mode departure schedules, and selecting travel routes both within islands and between islands. The cost components considered include inter-island travel costs, land travel costs, costs at selective points, and costs waiting for departure. A numerical experiment was conducted on the case of planning a tourist route in Maluku, Indonesia. The departure day scenario is built to find out the exact route and schedule on each day of departure with a minimum total cost. In addition, comparisons were also made to the results obtained in the time minimization model that was introduced earlier. The results showed that the model can adapt through variations of solutions to changes in the given parameters and objectives.